RANCANG BANGUN PENGAMAN PINTU PERSONAL ROOM MENGGUNAKAN SENSOR SIDIK JARI BERBASIS ARDUINO - Hengky Yalandra; Putra Jaya (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
The development of a personal room door security system needs to be improved, due to the high crime rate of theft. Personal room is a room that is private and feels to have important things in it. The design and manufacture of this tool aims to create a personal room door security system that uses fingerprint sensors and touch sensors as input functions. This system uses Arduino as the system's main controller. The output component uses a doorlock solenoid, 16x2 LCD and buzzer. The doorlock solenoid functions as a personal room door lock, 16x2 LCD monitors the work process of the system, and buzzer as a sound indicator. Based on the testing and analysis conducted, it was concluded that the personal room door security system could work well. The system can open the door using a fingerprint sensor or touch sensor, so it can improve the personal room door security system. Keywords: Fingerprint sensor, Touch sensor, Arduino, Doorlock Solenoid, 16x2 LCD.